On the use of the Prandtl mixing length model in the cutting torch modeling. - Mancinelli, Beatriz (2011)
The Prandtl mixing length model has been used to take into account the turbulent effects in a 30 A high-energy density cutting torch model. In particular, the model requires the introduction of only one adjustable coefficient c corresponding to the length of action of the turbulence. It is shown that the c value has little effect on the plasma temperature profiles outside the nozzle (the differences being less than 10 %), but severely affects the plasma velocity distribution, with differences reaching about 100 % at the middle of the nozzle-anode gap. Within the experimental uncertainties it was also found that the value c = 0.08 allows to reproduce both, the experimental data of velocity and temperature.